Modified robotic-assisted laparoscopic pyeloplasty in children for ureteropelvic junction obstruction with long proximal ureteral stricture: The “double-flap” technique - Han, Ce; Ma, Lifei; Li, Pin; Wang, Jia’nan; Zhou, Xiaoguang; Tao, Tian; Cao, Hualin; Tao, Yuandong; Yang, Yunjie; Zhao, Yang; Zhu, Weiwei; Guo, Tao; et al. (Frontiers in Pediatrics, 2022)
Objective The objective of this study is to introduce a novel technique of robotic-assisted laparoscopic pyeloplasty (RALP) for ureteropelvic junction obstruction (UPJO) with long proximal ureteral stricture in children. Materials and methods Clinical information on patients who underwent a modified RALP between July 2018 and May 2019 in our center was collected retrospectively. Our surgical modifications mainly include “double-flap” tailoring of the renal pelvis and anastomosis of spatulate ureter with the double-flap. Demographic, perioperative, postoperative, and follow-up information was recorded in detail. Results A total of 13 patients were included in the study. All the patients underwent a modified RALP without conversion to open surgery. They were followed up with a median time of 36 months. The anteroposterior diameter of the renal pelvis was 1.19 ± 0.21 at 6 months after the surgery, which was significantly lower than that on admission (3.93 ± 0.79). The split renal function of the children was also significantly improved from 0.37 ± 0.05) to 0.46 ± 0.02 at 6 months after surgery (p < 0.05). The diuretic renography revealed that all the patients have a T1/2 time less than 20 min postoperatively. The children were in good condition during the follow-up period. Conclusions Modified RALP is an effective surgical treatment for children with UPJO with long proximal ureteral stricture. The success rate of this modification has been preliminarily confirmed.